Building the Character of Children Through Non-Formal Education in Schools - Widodo, Widodo; Nusantara, Widya (Universitas Negeri Semarang, 2020)
The research objective is to determine the role of Non-formal Education (NFE) programs in schools and childrenâ€™s interest in Non-formal Education The study uses a quantitative analysis approach. The results show there is a holistic and synergistic relationship between Non-formal Education and schools. The interest of students who take the Non-formal Education program at school is â€œoptionalâ€, there is no compulsion, according to studentsâ€™ interests, is entertaining, gives â€œadded valueâ€ to children. NFE program analysis that strengthens the character of children includes; sports specialities strengthen the character of sportsmanship, tenacity and courage. An additional program of subject matter reinforces the character of diligent learning. The culinary training program strengthens character not to give up and the Islamic arts program strengthens creative character. Non-formal education is really needed to support the character in extracurricular in formal education NFE program in schools is very useful to provide reinforcement of positive character and even become a â€œmustâ€ so that studentsâ€™ character develops well.